Effects of the number of wells on the performance of green InGaN/GaN LEDs with V-shape pits grown on Si substrates. (February 2018) - Wu, Qingfeng; Zhang, Jianli; Mo, Chunlan; Wang, Xiaolan; Quan, Zhijue; Wu, Xiaoming; Pan, Shuan; Wang, Guangxu; Liu, Junlin; Jiang, Fengyi
Abstract: The effect of the number of wells on quantum efficiency and forward voltage of vertical green InGaN/GaN multiple quantum wells (MQWs) light-emitting diodes (LEDs) grown on Si substrate has been experimentally investigated. We have prepared three LED samples with 3, 5 and 7 wells. Electroluminescence measurement shows that the LED with 5 wells has the highest external quantum efficiency (EQE) and the lowest forward voltage. It is observed that V-shaped pits grow up in size and density with an increase in quantum well number by means of scan electron microscope. Due to more hole injection via V-shaped pits, a larger area ratio of pits as a result of more number of wells would bring a lower forward voltage and a higher EQE. However, besides the increasing series resistance would bring a higher forward voltage, the interface of MQWs would become rougher and deteriorate the emission efficiency when increasing the wells number. Highlights: V-shaped pits grow up in size and density with an increase in quantum well number. A larger area ratio of pits would bring a lower forward voltage. The interface of MQWs would become rougher with increase of wells number.